2011
DOI: 10.1002/stem.562
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Wnt-4 and Wnt-11 During Retinoic Acid-Induced Neuronal Differentiation

Abstract: Retinoic acid and Wnt/β‐catenin signals play important roles during neuronal differentiation but less is known about noncanonical Wnt signals in this context. We examined retinoic acid and Wnt signaling in two human embryonal carcinoma cell lines, NTERA‐2 (clone D1), which undergoes neuronal differentiation in response to retinoic acid, and 2102Ep, which does not. Retinoic acid treatment inhibited β‐catenin/Tcf activity in NTERA‐2 cells but not in 2102Ep cells. Inhibition occurred downstream of β‐catenin but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 72 publications
11
43
0
Order By: Relevance
“…It has been demonstrated that activation of Notch signaling results in increased microtubule stability and changes in axonal morphology and branching (21). Similarly, Wnt2 promotes cortical dendrite growth and dendritic spine formation and Wnt11 early neurogenesis (22,23). Because VEGF-induced signaling is complex and intersects with multiple pathways, we tested whether inhibition of PI3K or Notch signaling resulted in functional changes of VEGF-induced neurite growth.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that activation of Notch signaling results in increased microtubule stability and changes in axonal morphology and branching (21). Similarly, Wnt2 promotes cortical dendrite growth and dendritic spine formation and Wnt11 early neurogenesis (22,23). Because VEGF-induced signaling is complex and intersects with multiple pathways, we tested whether inhibition of PI3K or Notch signaling resulted in functional changes of VEGF-induced neurite growth.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies highlight the critical role Wnt signaling plays in NSCs, but the nature of the Wnt signals involved remains unclear, with reports of increased and decreased Wnt signaling taking place during differentiation [68,175] and disease [176,177]. Neurogenesis in the hippocampus, where Wnt signaling plays important roles, is gradually lost as we age [178], and this loss is implicated in neurodegenerative diseases [123].…”
Section: Discussionmentioning
confidence: 99%
“…Induced proliferation of hESCs/mNSCs [65,66] Recombinant Wnt-3a Induced proliferation and differentiation of hESCs [67] Wnt-4 silencing Impaired early differentiation in hECCs [68] Wnt-5a KO Impaired neurite development in the olfactory bulb (OB) [44] Wnt-1 and Wnt-5a DKO Impaired neurogenesis of midbrain dopaminergic neurons [52] Wnt-5a KO Impaired axon growth and guidance of dopaminergic neurons [45] Wnt-5a CM Increased synaptogenesis and maturation of hippocampal progenitors [69,70] Wnt-5a overexpression Induced axonal differentiation in hippocampal cultures [71] Wnt-7a KO Delayed morphological maturation of glomerular rosettes and synapsin I accumulation [46] Wnt-7a KO Impaired ventral midbrain neurogenesis [47] Wnt-7a and Dvl DKO Defective spine morphogenesis and mossy fiber-CA3 synaptic transmission [48] Wnt-7a Proposed as a key element in the regulation of NSC self-renewal/differentiation; altered spindle- Canonical Wnt receptors are also important for correct neural development (Table 2): FZD3 KO mice show impaired axonal guidance [73] while LRP6 KO mice present cortical defects [74]. Also, FZD1 has been shown to be the receptor for canonical Wnt-1 in mouse tyrosine hydroxylase positive neurons, which activates β-catenin-dependent signaling promoting neuroprotection in dopaminergic neurons [75].…”
Section: Neural Phenotype In Mammalian Models Referencementioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus β-catenin can act as a transcription factor (along with its cofactors TCF/LEF) to promote gene transcription of effectors of Wnt signalling, such as c-myc and cyclin D2. In contrast, the non-canonical pathways, such as those stimulated by Wnt4 are β-catenin independent and have been shown to antagonise the canonical Wnt pathway in several cell types [13,14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%